Katagorisasi Ayat Makki Dan Madani: Pengertian, Ciri, Hikmah Dan Cara Mengetahui Makkiyah Dan Madaniyah - abd halik; Abd haris; Supandi Supandi (STAI Al-Mujtama Pamekasan, 2022)
The Qur'an revealed to this world is a guide and a mercy to humans in this world, because the Qur'an is solely to help mankind as a guide for their life. People who read the Qur'anul Karim are expected not only to know how to read it but are also expected to be able to understand the contents of the content, therefore, the methodology of understanding the Qur'an needs to be known and studied in order to have more faith in the Qur'an. 'an is getting stronger. In terms of verse division, the scholars classify the verses in the Qur'an, there are differences in determining the verses and letters that were revealed in the city of Mecca and the verses that were revealed in the city of Medina so that they the scholars define Makkiyah and Madaniyah. Makkiyah is what was revealed in Mecca, even though it was revealed after the hijrah, Madaniyah is what was revealed in the city of Medina so that from this definition the word contains three elements, namely 1) Time, 2) Location and 3) The target of the verses and letters that were revealed. Place criteria as the basis for classification without considering its effect on the text in terms of content and form. In addition to the criteria above, there are other criteria that are used to distinguish between makki and civil. Keywords: Makki, Madani